Accounting Information System for Calculating Remaining Profits from Cooperative Operations Using the Direct Method at Primkoppol Belawan Port Resort - Zhuria Widiasih (International Journal of Mechanical Computational and Manufacturing Research, 2023)
Primkoppol Belawan Port Resort is the Agency and Implementer of Cooperatives at the Polres Level, also assists in the implementation of the Cooperative work program and policies underlined by the North Sumatra Police and Puskoppolda Leaders in an effort to assist Leaders in realizing the welfare of members of the Police and Civil Servants of the Police and their families, which is carried out by raising funds from members and channeling/financing in the real business sector. there are also those who say that Primkoppol Belawan Harbor Resort is a microfinance institution that can and is able to serve the needs of members based on a profit sharing system. As happens in every company, both government-owned and private companies have relatively large numbers of transactions, so a database is needed that can store and process the data efficiently, quickly and can be used at any time when needed. Primkoppol Belawan Harbor Resort is a private financial institution engaged in savings and loan services. Primkoppol Belawan Resort Resort's activities are inseparable from members' savings and loan transactions, so a computerized system is needed so that transactions run well. This information system was built using Visual Basic 2010 and SQL Server 2008 as the database. Primkoppol Belawan Resort Resort's activities are inseparable from members' savings and loan transactions, so a computerized system is needed so that transactions run well. This information system was built using Visual Basic 2010 and SQL Server 2008 as the database. Primkoppol Belawan Resort Resort's activities are inseparable from members' savings and loan transactions, so a computerized system is needed so that transactions run well. This information system was built using Visual Basic 2010 and SQL Server 2008 as the database